Utilizing Technology Acceptance Model in Technical and Usability Evaluation of The Developed Tourism SMEs Social Media Analytics Tool - Madila, Shadrack Stephen (Universitas Bina Darma, 2024)
The tourism sector is among the most profitable sectors with a high contribution to the world economy. The majority of tourism organisations are operated as small and medium-sized enterprises (SMEs). These tourism SMEs adopted the use of ICT in their businesses. Social media analytics (SMA) is the process of evaluating and analysing social media data and getting insight from it for business decision-making. In this study, the social media analytics tool was developed based on tourism SMEs managers and owner’s requirements. The aim of this study is to utilise technology acceptance model (TAM) to evaluate the developed social media analytics tool for tourism SMEs. The social media analytics tool was developed based on tourism SMEs requirements and followed TAM construct of perceive ease of use and perceive usefulness. The developed tool was hosted and participants were invited to conduct the evaluation process. 10 ICT personnel conducted the technical evaluation of the system while 15 end users of the system participated in usability evaluation. The findings show that the majority of the technical evaluation participants were satisfied with the technical aspect of the developed social media analytics tool. Usability evaluation results show that the participants were satisfied with the ease of use of the tool, the interfaces of the tool and they all agreed that the developed system modules are useful to tourism SMEs and they will recommend the tool to other SMEs managers and owners. The study recommends the use of TAM model in developing and evaluation of the developed IT systems. The technical evaluation aspect seems to be few; hence the study recommends on the future versions of the tools the technical evaluation aspect to be increased during evaluation.